2021
DOI: 10.3390/ijms22126214
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence: Pathogenic Mechanisms in Lung Fibrosis

Abstract: Pulmonary fibrosis is a chronic and fatal lung disease that significantly impacts the aging population globally. To date, anti-fibrotic, immunosuppressive, and other adjunct therapy demonstrate limited efficacies. Advancing our understanding of the pathogenic mechanisms of lung fibrosis will provide a future path for the cure. Cellular senescence has gained substantial interest in recent decades due to the increased incidence of fibroproliferative lung diseases in the older age group. Furthermore, the patholog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 199 publications
0
37
0
3
Order By: Relevance
“…In vivo senescent endothelial cells of animal models and human tissues have been identified in different pathological conditions [25]. For example, senescence-associated beta-galactosidase (SA-β-gal) dye [26] is a commonly used marker to recognize cellular senescence, and it has revealed an increase of senescent endothelial cells in diabetic Zucker rats [27,28].…”
Section: Factors That Induce Endothelial Senescencementioning
confidence: 99%
“…In vivo senescent endothelial cells of animal models and human tissues have been identified in different pathological conditions [25]. For example, senescence-associated beta-galactosidase (SA-β-gal) dye [26] is a commonly used marker to recognize cellular senescence, and it has revealed an increase of senescent endothelial cells in diabetic Zucker rats [27,28].…”
Section: Factors That Induce Endothelial Senescencementioning
confidence: 99%
“…Although new therapies significantly increased the duration and quality of life of IPF patients, a therapeutic regimen that can arrest or, even better, reverse disease progression remains to be discovered [ 4 ]. Partly responsible for this situation is our limited understanding of the cellular states and processes that each of the more than 40 cell types in the lung undergoes, in an active (causative) or reactive manner in homeostatic and injury contexts [ 5 , 6 ]. A number of recent studies clearly identified the chronic injury of the alveolar type 2 epithelial cells (AEC2s) as the initial site of injury in the IPF lung [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our PPI network analyses suggested that AT2 senescence and progenitor arrested state in the setting of a ViP/sViP-immune response (cytokine storm contributed by PBMCs) may support a SASP phenotype, which is a pathological feature of aging and IPF lung. 97 , 98 …”
Section: Discussionmentioning
confidence: 99%